Correlation of P53 Expression with Clinicopathological Parameters, Hormone Receptors and HER 2 Neu Status in Breast Carcinoma - Ali, Tahmida; Kamath, Sulatha M (Asian Pacific Journal of Cancer Biology, 2022)
Background: Progesterone receptor (PR), estrogen receptor (ER) expression, human epidermal growth factor 2 (HER 2 neu) amplification/ overexpression, and p53 nuclear protein accumulation are all significant prognostic biomarkers in breast cancer (BC). This work aims to assess the co-presence of p53 overexpression with ER, PR, and HER 2 neu expression in invasive BC specimens by IHC and compare their expression with various clinicopathological features. Objectives: To evaluate the expression of ER, PR, HER-2neu and p53 in invasive breast carcinoma specimens and to correlate the expression of p53 with ER, PR, HER-2 neu and the clinicopathological parameters. Methods: Cases of Modified Radical Mastectomy received from June 2015 to May 2017 were studied. In addition to hematoxylin and eosin sections, immunohistochemical staining was done for ER, PR, HER 2 neu and p53. The expression of ER, PR, HER 2 neu and p53 was noted and the findings were correlated with other clinicopathological parameters. Results: Among 86 cases studied most of them belonged to the age group 41-60 years (54, 62.8%). A significant positive correlation of p53 over expression with ER and PR positive tumours and Triple Negative tumours was noted. Also p53 overexpression showed a positive significant correlation with tumour grade. Conclusion: P53 overexpression in breast carcinoma indicates an aggressive clinical course and can be used as a marker of poor prognosis.